ВЕРБАЛНА И АУДИТИВНА ПЕРЦЕПЦИЈА КАЈ ЛИЦА СО СЛУШЕН АМПЛИФИКАТОР И КОХЛЕАРЕН ИМПЛАНТ - Лазаровска Весна; Давчева Чакар Марина; Ѓорѓеска Билјана; Јовановска Мира (Medical Faculty, Ss. Cyril and Methodius University in Skopje, 2012)
Verbal and auditory (hearing) perception is a subjective experience of one acoustic stimulus of different form and origin (tone, noise, speech, murmur, roar). These perceptions include reception of hearing stimulus, signals and acoustic signs, their processing and retaining (storing). Ability for auditory and verbal perception in a hearing disabled person is much lower or fully disabled. It depends on the level and type of hearing disability and type of amplification. The aim of this paper was to define the level of improvement of hearing and verbal perceptions in hearing disabled persons. A total of 31 patients were included in the study from the University Clinic for Ear, Nose and Throat in Skopje, with a diagnosis of severe bilateral hearing disability. After being diagnosed, they were included into a rehabilitation program and tested, with hearing aids. After six months period, the results of the conducted test for development of auditory perception-Lip Profile (listening progress) showed an insignificant improvement of auditory and verbal perception comparing to the period when the subjects were without hearing aids. Due to the minor improvement, the same patients were included into a treatment with insertion of a Cochlear implant. Conclusion: After six months - period of rehabilitation treatment there was a significant improvement of auditory and verbal perception in comparison with the period when patients had hearing aids.
Keywords: auditory perception; verbal perception; hearing aid; cochlear implant; speech therapies treatment